Histological and Anatomical Study of Cluster Pregnancy in Abortion Women at Al-Zahraa Teaching Hospital - Zainab Sajid Mohammed (Journal of Global Pharma Technology, 2016)
The contemporary revision was accompanied at Al-Zahraa-Teaching -Hospital for Obstetrics. This research comprised a histo-pathological study of women distress from cluster pregnancy in Najaf Governorate, who reviewed the obstetrics department at Al-Zahraa-Teaching-Hospital for the period from 1/9/2017 to 5/2/2018.About (10) of women with cluster pregnancies, (5) cases of complete cluster pregnancies and (5) cases of partial cluster pregnancy. The range age of women with cluster pregnancies ranged from (25-15) y. The consequences of the anatomical and histological revision of women with cluster pregnancy showed that there were two types of cluster pregnancies: full cluster pregnancy and partial cluster pregnancy. Also revealed that the placenta and the fetus looked as a block on the fluid-filled bags analogous to the grape cluster where the size of these bags about (8 * 8). It was also distinguished that the fetus and placenta were not distinctive in a clear and completely slanted. However the results indicated for women with partial cluster pregnancy that the fetus and a bulky partition of the placenta appeared in the form of a mass container on the bags filled with liquids, which were in the form of irregular clusters similar to the cluster of grapes, where the size of these bags about (5 * 5) .As noted that the fetus completely mutilated or non-existent but a minor portion of the placenta lingered intact and distinctive.Keywords: Molar pregnancy, Partial molar pregnancy, Abortion woman.